Design and Analysis of a Candlenut Shell Breaking Machine - Zulhendri; Yuliarman; Adril, Elvis; Contrian Pratama, Yudha (IJIMCE : International Journal of Innovation in Mechanical Construction and Energy, 2024)
Candlenut seeds are one of the plants that grow in Indonesia. Candlenut leaves and seeds have many benefits that are useful for human life. Candlenut oil can be used as a raw material for making varnish, paint, soap, fabric oil, resin, synthetic leather, lubricants, compost, and cleaning or polishing mixtures. Candlenut fruit has a shape ranging from oval to round, green to brownish green, with a length of ± 5–6 cm and a width of ± 5-7 cm. One candlenut contains one to three candlenut seeds. To get the candlenut seeds, they must be removed from their hard and thick shell by breaking them.So far, getting candlenut seeds has been done by breaking them manually by hitting them one by one. This is certainly not effective and takes a long time. Based on this, a tool was designed and made for breaking candlenut shells using a 2 HP motor drive. This candlenut shell breaker tool consists of a throwing part that rotates vertically, which, due to the centripental effect, throws the candlenut kernels against the wall of the breaker. The broken candlenut kernels and shells fall down into the filter section to separate the kernels and shells, then the candlenut kernels go inside. holding containers. To get the ideal launcher rotation, several speed variations were tested, namely: 1. 250 rpm, 2. 350 rpm, and 3. 500 rpm. Of the three variations of rotation, the best rotation was obtained with the shell breaking and the seeds releasing well without breaking, namely at 350 rpm.